Struktur Anatomi Akar, Batang dan Daun Gaharu (Aquilaria malaccensis Lamk.) yang Mengalami Cekaman Kekeringan - Dwi Gusmalawati, Suharti, Mukarlina, (Universitas Tanjungpura, 2017)
Agarwood (Aquilaria malaccensis) is a commodity of Non-Timber Forest Products (NTFPs), which has the result of the agar with the best quality and high value. Drought stress can impede the growth of the agarwood plant which can affect its morphology and anatomy. This research aims to determine the anatomical structure of the root, stem and leaf of the agarwood (A. malaccensis) that experiences drought stress. The research was conducted from July to October 2016. The drought stress in treatment (KL 25%) resulted in cross section of roots and stems of agarwood to have the length and thickness of cortical cells that becomes larger with a rectangular shape, in addition, the treatment (KL 25%) also resulted in the size of mesophyll tissue cells to become smaller.